Pulmonary Cryptococcus infections as a manifestation of idiopathic CD4 lymphocytopenia: case report and literature review - Christina S. Thornton; Oscar Larios; Jennifer Grossman; Thomas P. Griener; Steven Vaughan (BMC Infectious Diseases, 2019)
Abstract Background Idiopathic CD4 lymphocytopenia (ICL) is a rare clinical disease with relative CD4 deficiency in the absence of HIV infection. The pathogenicity of ICL is poorly understood with an unclear incidence rate in the general population. Sequelae of ICL includes AIDS-defining infections, which most commonly includes Cryptococcus neoformans. Typically, C. neoformans infections present with CNS involvement but rarely with extra-CNS manifestations. Here, we present a rare case of ICL with exclusively primary pulmonary cryptococcus and a review of the literature. Case presentation A 56-year-old female presented to our tertiary care hospital requiring a right hip open reduction intervention. The patient became febrile during admission, prompting a work-up that included a chest X-ray showing a peripheral pulmonary solitary nodule. Transthoracic biopsy revealed encapsulated yeast forms in keeping with C. neoformans. CD4 counts, repeated at least one month apart, were < 200 cells/mm3, with negative HIV testing. Flow cytometry and genetic testing were completed to elucidate the etiology of the immune deficiency, both of which were unremarkable. She was subsequently treated with 12 months of posaconazole with clinical resolution. Conclusions Our patient highlights a rare clinical disease, which a review of literature revealed only five cases in the literature with exclusive pulmonary Cryptococcus in ICL/ This case demonstrates the strong clinical acumen required to properly diagnose and ultimately manage the patient.